Preperitoneal pelvic packing in patients with hemodynamic instability due to severe pelvic fracture: early experience in a Korean trauma center. Issue 1 (December 2016) - Jang, Ji; Shim, Hongjin; Jung, Pil; Kim, Seongyup; Bae, Keum
Abstract Background The mortality rate of patients with hemodynamic instability due to severe pelvic fracture is reported to be 40–60 % despite a multidisciplinary treatment approach. Angioembolization and external fixation of the pelvis are the main procedures used to control bleeding in these patients. Several studies have shown that preperitoneal pelvic packing (PPP) is effective for hemorrhage control, despite being small and observational in nature. The purpose of this study was to describe a Korean trauma center's early experience with PPP in unstable patients with pelvic fractures and to evaluate its effectiveness. Methods Between January 2012 and May 2015, 30 patients with hemodynamic instability caused by pelvic fracture were enrolled in this study. PPP has been performed in 14 patients since May 2014. Data of pelvic fracture patients with hemodynamic instability were selected from Wonju Severance Christian Hospital Pelvic Trauma Database and were analyzed retrospectively. Results Mean age and mean ISS were 60.4 ± 18.8 years and 39.2 ± 8.1 in 30 unstable patients with pelvic fracture. Mean SBP was 89.1 ± 24.7 mmHg, and mean hemoglobin was 10.6 ± 2.3 g/dL. When the non-PPP group (16 patients) and the PPP group (14 patients) were compared, there was no significant difference in the age, gender, ISS, and occurrence of associated injury (p  = 0.82, p  = 0.23, p  = 0.92, andp  = 0.60, respectively). Mortality rate due to acute hemorrhage were 37.5 % in the non-PPP group and 14.3 % in the PPP group. In the PPP group, three patients underwent PPP in the hybrid operating room, and a laparotomy was performed in three patients. Mean systolic blood pressure increased significantly after PPP (71.6 ± 9.8 vs. 132.2 ± 36.4 mmHg, p  = 0.002). Conclusions In unstable patients with pelvic fractures, PPP can be used as an effective treatment, complementary to AE, to control pelvic bleeding.